?ANAL YSIS OF PROHIBITED AMINE IN Azo DYES USED IN TEXTILE AND LEATHER GARMENTS (Biological Sciences - PJSIR, 2000)
The dyes based on specific 20 arylamines have been used on industrial scale due to their desirable colouring properties. These dyes release these amines under different environmental and physiological conditions and have been established to be potentially carcinogenic in nature. Therefore, trace level determination of these prohibited amines is of great practical importance. The present review embodies details of various methods used for their determination. These methods spelt out procedures and techniques for the quantitative determination of these amines under chromatogenic spot test, spectro- photometric method, chromatographic method, potentiometric titration and polarographic estimation. Various reagents and colour reactions are described for spot tests and spectrophotometric determinations. The techniques such as column chromatography, thinlayer chromatography, gas chromatography, gas liquid chromatography, high performance liquid chromatography and optical densitometry have also been reported. Various columns and solvent systems arc described for the separation of a mixture of amines. The potential and limitations of various methods have also been discussed in the light of our practical experience.